BARBİTURİK ASİT HALKASI İÇEREN METAKRİLAT POLİMERLERİN SENTEZİ VE ADSORBSİYON ÇALIŞMALARI - TORGUT, GÜLBEN (Fırat Üniveristesi, 2009)
Bu çalışmada, önce farklı oranlarda metil metakrilat-malonesteri kopolimerleri 1,4-dioksan çözeltisinde serbest radikal polimerizasyonuyla 60 °C'de 2,2'-azobisisobutironitril ile sentezlendi. Hazırlanan polimerler üre ile modifiye edildi ve farklı oranlardaki poli(St-co-BAMA) polimerleri hazırlandı. Kopolimerlerin yapısı FT-IR ve 1H-NMR ile karakterize edildi. Oda sıcaklığında kopolimerlerin boya tutma özellikleri araştırıldı ve birbirleriyle karşılaştırıldı.Bütün polimerlerin dielektrik özellikleri impedans analizör yardımıyla farklı frekanslarda ölçüldü. Dielektrik geçirgenlikleri ve dielektrik kayıpları oda sıcaklığında ölçüldü ve sonuçları birbirleriyle karşılaştırıldı. Bütün polimerlerin dielektrik özelliklerine ilaveten sabit frekanslarda ve değişik sıcaklıklarda da ölçüldü. Kopolimerlerin termal ölçümleri TGA ve DSC ile yapıldı. TGA tekniği kullanılarak Kissinger metoduyla farklı ısıtma hızlarında bozunmaya yönelik aktivasyon enerjileri ölçüldü.Anahtar kelimeler: Barbiturik asit, Adsorpsiyon, Dielektrik özellikler, Termal özellikler

In this study, St-MMA having malonester side group,copolymers that have different ratios were synthesized at 60°C in a 1,4-dioxane solution in the presence of AIBN by free-radical polymerization. These polymers were modified with urea and were synthesized poli(St-co-BAMA) that have different ratios. These polymers were characterized by FT-IR and 1H NMR.Dye uptake properties of polymers were investigated at room heat. Also dye uptake properties were investigated different temperature and results were compared.Dielectric properties of all polymers were measured at different frequencies by impedance analyzer. Dielectric permittivity and dielectric loss were measured at room heat and were compared with each other. In addition to dielectric properties of all polymers were measured at different temperature in constant frequences and were compared with each other.Termal measurements of all polymers were carried out by TGA and DSC. The activation energies were measured by TGA at different heating rate by Kissinger method.Keywords: Barbituric acid, Adsorption, Dielectric properties, Termal measurements
Synthesis methacrylate polymers which containing barbituric acid and adsorption studies
Keywords: Polimer Bilim ve Teknolojisi